Hidradenocarcinoma presenting as soft tissue mass: Case report with cytomorphologic description, histologic correlation, and differential diagnosis. Issue 5 (15th February 2016) - Jinnah, Alexander H.; Emory, Cynthia L.; Mai, Nicholas H.; Bergman, Simon; Salih, Ziyan T.
Abstract : Hidradenocarcinoma (HAC) is a rare adenexal tumor with a propensity for the head and neck region and extremities. We report a case of hidradenocarcinnoma in a 56‐year‐old woman with a mass on her right palm sampled by fine‐needle aspiration and later confirmed on histological examination. Fine‐needle aspiration cytology revealed a dual population of cells including polyhedral eosinophilic cells and glycogen containing cells with pale/clear cytoplasm. The nuclei were pleomorphic with prominent nucleoli. Occassional papillary structures were identified on the cell block material. A series of immunohistochemical stains were performed and an adnexal neoplasm was suggested. The mass was resected. On histologic sections, infiltration into the adjacent soft tissue was identified. After an additional series of immunohistochemical stains, the diagnosis was confirmed as a HAC. Herein, we present our findings and discuss the differential diagnoses. Diagn. Cytopathol. 2016;44:438–441. © 2016 Wiley Periodicals, Inc.